COMPLEX APPROACHES TO TREATMENT OF DYSLIPIDEMIA IN PATIENTS WITH ISHEMIC HEART DISEASE - M. A. Chichkova; O. Sh. Oynotkinova; N. V. Kovalenko; A. A. Abdulkerimova; M. U. Chichkov; V. N. Mescheryakov (Архивъ внутренней медицины)
The risk of coronary heart disease increases significantly with an increase in blood cholesterol and low density lipoprotein (LDL). We know that is not always standard therapy fails to achieve target numbers of blood lipids in patients with coronary artery disease. We examined 100 patients with coronary heart disease (CHD): stable angina II-III functional — study group (60 patients) and control group (40 patients). The studies we have obtained evidence that the combination of plasmapheresis, ultraviolet blood irradiation and statins to reduce total cholesterol in patients IIFK 2,7% IIIFK 23,3%, LDL cholesterol in patients IIFK 30,4%, IIIFK 37,3% (r<0,05). Following the combination therapy achieved level of hyperlipidemia can be maintained with lower doses of statins.